2020
DOI: 10.3390/ijerph17030801
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Properties on K Factor in the Granite and Limestone Regions of China

Abstract: Soil erosion has become a serious ecological problem in many catchments. Soil erodibility K factor can be estimated based on a series of soil properties, however, the identification of dominant soil properties that affect K factor prediction at different soil types has been little concerned. In this study, 3 soil profiles from the Jiulongjiang River Catchment (JRC) of granite region in Fujian province and 18 soil profiles from the Chenqi Catchment (CC) of karst region in Guizhou province were selected. Soil pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The organic matter in soil increases infiltration rates of precipitation through soil horizons. The high infiltration rates decrease surface runoff and reduce soil erosion and the K-factor by forming stable soil aggregates with organic matter [ 58 , 59 ]. In general, loss of soil organic matter due to degradation (from land-use practices) can significantly alter its physical properties, namely pore size, bulk density, aggregation, and water-holding capacity in soils [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The organic matter in soil increases infiltration rates of precipitation through soil horizons. The high infiltration rates decrease surface runoff and reduce soil erosion and the K-factor by forming stable soil aggregates with organic matter [ 58 , 59 ]. In general, loss of soil organic matter due to degradation (from land-use practices) can significantly alter its physical properties, namely pore size, bulk density, aggregation, and water-holding capacity in soils [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the OC flux is reported from input derived from various terrigenous sources, including old soil. Thus, the K factor in catchments could have variable results based on the parent soil type [ 58 ]. They conclude that the K-factor depends mainly on texture in granitic terrains, whereas in limestone-derived soils, OM plays a crucial role.…”
Section: Discussionmentioning
confidence: 99%
“…The highest percentage of very fine sand fraction belongs to the steep slope class. The high content of very fine dust and sand can cause the soil to be sensitive to erosion or in other words the erodibility index increases [13]. Very fine sand reduces the ability of the soil to transmit water due to blockages in the pore spaces of the soil, thus increasing the occurrence of run off.…”
Section: Fig 2 Percentage Of Silt and Clay Fractionsmentioning
confidence: 99%
“…In terms of basin-scale analysis of soil erosion, highlighting the impact of soil properties and external influencing factors on soil erodibility has attracted widespread attention in the southwest karst area of China. For instance, Liu et al (2020) applied the EPIC model to analyze erodibility variations of agricultural abandonment in the typical karst catchment of Guizhou province and found that the K -factor in the TOC (total organic carbon)-rich soils (>2%) is mainly influenced by soil particle distribution, while that in the TOC-poor soils is mainly determined by SOM (soil organic matter). Feng et al (2016) also found that tillage disturbances increase the average annual soil loss rate from 2006 to 2011 in a partially cultivated peak-cluster depression basin of northwestern Guangxi.…”
Section: Introductionmentioning
confidence: 99%